The Effect of Exposure to Positive Indonesian National Army News on Covid-19 in Online Media on the Attitudes of the People of Bajawa City - Silvinus Wou; Petrus Ana Andung; Fitri Titi Meilawati (COMMENTATE: Journal of Communication Management, 2021)
One of the news that has caught the attention of the Indonesian people since 2019 until now is the news about Covid-19. The purpose of this study was to analyze the effect of exposure to 41 TNI reports that were positive for Covid-19 in online media on people's attitudes in Bajawa City. The approach in this research is quantitative with a survey method. The sampling technique used is the purposive sampling technique and the sample obtained is 100 people. The theory used in this research is the Agenda setting theory. The study results found that there was an influence between news exposure of 41 soldiers with positive Covid-19 in online media towards people's attitudes in Bajawa City. This is evidenced by the presence of some respondents who are more afraid of news of death due to Covid-19 and do not understand how to prevent Covid-19.